Assistance in Implementing a Solar-Powered Ultrasonic Pest Repellent for the Sekar Murni Farmer Group, Semawot Village - Putri liana; M Jauhar Vikri; Roihatur Rohmah (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Rat infestations remain a major challenge affecting rice productivity in rural agricultural areas. This community service program aimed to improve farmers’ knowledge and technical skills in implementing a solar-powered ultrasonic pest repellent equipped with an automatic light sensor as a safer and more environmentally friendly alternative for rat control. The program involved 15 representatives of the Sekar Murni Farmers’ Group in Semawot Village, Bojonegoro Regency, and was conducted through observation, outreach, hands-on training, and evaluation using pre-test, post-test, and participant satisfaction questionnaires. The average participant score increased from 53.2 to 86.6, with an N-Gain of 71.3%, indicating a high level of knowledge improvement. During field implementation, the device operated reliably under actual rice field conditions, and farmers informally reported reduced rat activity around the installation area, although these observations were not quantitatively verified. Participants also expressed positive acceptance of the technology because of its ease of operation and environmental safety. The integration of solar energy and automatic day-and-night operation distinguishes this program from previous community service initiatives. Overall, the program improved farmers’ knowledge, encouraged initial technology adoption, and demonstrated the potential of sustainable pest management to support agricultural productivity.